Papua New Guinea : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper analyzes the workings and effectiveness of the monetary transmission mechanism in Papua New Guinea. The paper is organized as follows: it describes the current institutional structure in Papua New Guinea; interest rate is discussed; the evidence from vector autoregression analysis on the relationship between monetary policy variables and output and prices is considered; finally, implications are included. The Bank of Papua New Guinea (BPNG) uses a reserve money framework to conduct monetary policy operations. A macroeconomic balance approach estimates the REER, which simultaneously achieves internal and external balance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet